Making Parents: First-Birth Ritual among the Ankave-Anga of Papua New Guinea - Bonnemère, Pascale (Journal for the academic study of religion, 2009)
Although the birth of children is a quite common event, it is not an easy experience for the Ankave-Anga women of Papua New Guinea, who have all heard of or even seen relatives die after delivery. The Ankave live in the far northern part of Gulf Province, far from its headquarters located on the southern coast, and do not yet have permanent church or health services that could accompany women in labour and save them in the event of difficulties. This situation may well have to do with the local importance of the rituals associated with the arrival of a first child, but this is not the point the paper would actually focus on. It would rather undertake an analysis of this ritual, which has the particularity of not being reducible to one specific moment but entails a series of gestures, attitudes, taboos and gifts that concern a wide range of kin and affines from the time when the pregnancy is known to the days that follow the birth. It is made up of secret gendered moments as well as public ones and results in a new parental pair that will thus become able to accomplish on their own what is needed for subsequent children to be fully integrated into the community. While these kinds of ritual have regionally been considered as one phase of male initiations (without much being said about it in the literature devoted to Anga groups; Herdt 1981, Godelier 1982), I argue that, among the Ankave (a southern Anga people), first-birth rituals are much more than the last stage of a male ritual cycle. The actions of everyone linked to the parents-to-be, together with the involvement of the parents themselves, point to both accession to parenthood for men and women alike and the expression of the avuncular relationship as a focus of the ritual.